Continuous simulation of the whole process of underwater explosion based on Eulerian finite element approach. (November 2018) - Liu, W.T.; Ming, F.R.; Zhang, A.M.; Miao, X.H.; Liu, Y.L.
Highlights: The whole process of underwater explosion is simulated continuously based on Eulerian finite element method. Underwater explosion bubble dynamics from continuous simulation and initialized from high-pressure gas are compared. The effects of shock wave propagation on the bubble motion near wall are analyzed by the coutinuous simulation. Abstract: Underwater explosion is an extremely complex hydrodynamic problem and it is always divided into two stages and studied individually, i.e., shock wave stage and bubble motion stage. Actually underwater explosion is a continuous process and there are intensive interactions between the two stages in some cases, e.g. underwater explosion in the vicinity of the wall. In this paper, the Eulerian finite element formulation considering the fluid compressibility is applied to continuously simulate the process of underwater explosion based on the subroutine of ABAQUS. Firstly, the governing equation and its solution by the operator splitting approach are discussed. Then the free-field underwater explosion is continuously simulated, including shock wave propagation and the bubble expansion, contraction, collapse, jet and rebound. The applicability and reliability of this method are discussed by comparing with experimental results from Klaseboer [5]. Furthermore, the traditional treatments of the simulation initialized at the bubble motion stage are discussed. Finally, the underwater explosion near wall is investigated regarding the interactions of shock wave and bubble motion and the importance of the continuous simulation of underwater explosion on the bubble motion characteristics is summarized.